A REVIEW OF THE ACCOUNTING ROLE IN ANCIENT AND COLONIAL PERIOD: A CASE STUDY OF INDONESIAN TELECOMUNICATION INDUSTRY - Bastian, Indra (Jurnal Akuntansi dan Keuangan Indonesia, 2006)
A development of accounting analysis has been a reflection of a linkage among government, industry and company. In this paper, the linkage has been legitimated as politicalfactors dominated a development of telecommunication industry and its companies. One of main findings is that accounting in Indonesia actually has been recognised since an ancient kingdom era. Some accounting practices, such as a tariff of upeti pnd mahar, have existed in ancient kingdom traditions. This means that accounting, whether in private and public sectors, has been implemented in the past. An economic recession has affected the telecommunication industry dramatically. Profit felt and a business slumped in the 1930s. A sustainability of colonial was a driver of a Japanese government’s policy on an Indonesian accounting education. The aim of the policy is to establish an administrative capability for a future colonisation government. In fact, the Indonesians took an advantage of this opportunity to support their independence movement. So, we can conclude that the accounting problems were unique in each period.